Effective Payroll Procedures Enhanced by Electronic Attendance Recording in Indonesia (Prosedur Penggajian yang Efektif Ditingkatkan dengan Pencatatan Kehadiran Elektronik di Indonesia) - Abidin, Fityan Izza Noor; Sari, Reni Ratna (Journal of Economics, Assets, and Evaluation, 2024)
This research investigates the effectiveness of accounting information systems in the payroll cycle of a company. Utilizing purposive sampling for interviews, the study evaluates the organizational structure's separation of responsibilities and payroll procedures, including staffing, attendance recording, payroll creation, and financial functions. Findings reveal that these practices are effectively implemented, aligning with theoretical expectations. However, an evaluation suggests that incorporating electronic attendance recording, such as fingerprint systems, could further enhance accuracy and reduce errors in attendance and overtime tracking.